TRANSFORMASI PERAN GURU PADA ERA ARTIFICIAL INTELLIGENCE DALAM PENDIDIKAN DASAR - Arifyana, Diana; Isdiyana, Aulia; Kamal, Rahmat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of Artificial Intelligence (AI) in the Society 5.0 era is transforming the professional identity of teachers in elementary education. This study aims to examine the transformation of teachers’ roles in the utilization of Artificial Intelligence (AI) and to identify the various challenges faced in its application in elementary school learning. The study employs a Systematic Literature Review (SLR) method, analyzing national journal articles published between 2021 and 2025. Data were collected through the identification, selection, and analysis of literature relevant to the use of AI in elementary education. The findings indicate that AI is shifting teachers’ roles from being the primary source of information to becoming facilitators, mentors, and managers of technology-based learning. AI also helps improve learning effectiveness, teacher creativity, and the efficiency of educational administration. However, the implementation of AI still faces challenges in the form of low digital literacy, limited facilities, and concerns regarding the diminishing of humanistic values in learning. Therefore, strengthening teachers’ digital competencies is a critical need in the digital age.